Subacute combined degeneration of the spinal cord of toxic etiology (clinical case) - A. A. Kondratov; A. S. Kotov (Русский журнал детской неврологии)
For more than two hundred years after its discovery, nitric oxide (I) has been widely used in medicine as an anesthetic, in the car industry as an engine performance enhancer, in the food industry as a preservative, and, unfortunately, among young people as a mild narcotic substance. Despite the widespread opinion that there is no harm from the use of “laughing gas” for recreational purposes, in the literature and in practice, there are a lot of cases when patients suffer from various complications, including neurological ones, caused precisely by the use of nitric oxide (I). One of the main mechanisms of the pathological effects of nitrous oxide on the nervous tissue is the inactivation of vitamin B12. This has been proven by studying the physicochemical properties of the gas, the effect on the organisms of laboratory animals, the change in the concentration of certain substances in the human body, and also by the use of cyanocobalamin for the treatment of these patients. This article describes a clinical case of the development of myelopolyneuropathy caused by the toxic effects of nitric oxide (I).